Functionality of screen advertising and its translation model (Eurasian Journal of Philology Science and Education, 2016)
The article considers the screen advertising functionality and its translation peculiarities. Today the commercial has a great impact on society, it influences lifestyle, it can be said that the commercial is the base of choice. Advertising has a wide functional range. The author identifies and describes the main functions of TV advertising. Much attention is given to the main problems of advertising translation process encountered by translators of television commercials. Having considered the theoretical material of the current topic and having analyzed screen advertising translation from English into Russian the author offers the advertising translation model. The model is illustrated by the analysis of the «Sonium» mobile phone advertising translation. The article brings us to the conclusion that TV advertisement should not be simply creative improvisation. In order to effectively translate advertisements, the translator must use an actively proven model of translation that would help transmit information to be equivalent in form to the original.
Keywords: screen (television) advertising; functionality; model of screen ads translation; translation strategy; conceptual correspondence; interpretation; perception.